Concepts of programming languages - Sebesta, Robert W (Boston : Pearson/Addison-Wesley, 2004)
This text should enable readers to critically evaluate different programming languages and choose the one most appropriate for a given application. It presents the principles, paradigms, designs and implementations of modern programming languages
Preliminaries -- Evolution of the major programming languages -- Describing sytax and semantics -- Lexical and syntax analysis -- Names, bindings, type checking, and scopes -- Data types -- Expressions and assignment statements -- Statement-level control structures -- Subprograms -- Implementing subprograms -- Abstract data types and encapsulation constructs -- Support for object-oriented programming -- Concurrency -- Exception handling and event handling -- Functional programming languages -- Logic programming languages
Includes bibliographical references (pages 651-660) and index
Keywords: Programming languages (Electronic computers)